A Review of the Hydrologic Response Mechanisms During Mountain Rain-on-Snow - Brandt, W. Tyler; Haleakala, Kayden; Hatchett, Benjamin J.; Pan, Ming (Frontiers in Earth Science, 2022)
Mountain rain-on-snow (ROS) generates large flooding events worldwide. Climate warming enhances the frequency, magnitude, and widespread nature of these events. Past studies indicate rainfall, not snowmelt, typically drives much of the runoff response during ROS. However, there is substantial event-to-event variability—resulting from shifting atmospheric drivers and nuanced physical mechanisms governing water flow through a snowpack. Historically, turbulent fluxes were assumed to dominate the energy balance for snowmelt during ROS. Recent research suggests that other components of the energy balance might be larger drivers depending on: (1) the time of year; (2) the elevation; and (3) the aspect of the slope. This mini review summarizes the literature on the physical processes governing ROS and proposes that moving forward we utilize the terms “active” and “passive” to describe a snowpack’s contribution (via snowmelt) to terrestrial water input (TWI) during ROS. Active snowpacks readily contribute meltwater to TWI via the energy balance, bolstering rainfall-runoff totals. Passive snowpacks do not melt, but simply convey rainwater through the snow matrix. In both snowpack cases, preferential flow paths enhance transmissivity. This proposed classification scheme will help researchers and water managers better communicate and interpret past findings, and aid in forecasting discussions of future events.